Practical Intrusion Analysis / Prevention and Detection for the Twenty-First Century - Trost Ryan (Addison-Wesley Publishing Company, 2010)
The only definitive guide to New-State-of-the-Art techniques in intrusion detection and prevention. Preface, Network Overview, Infrastructure Monitoring, Intrusion Detection Systems, Lifecycle of a Vulnerability, Proactive Intrusion Prevention and Response Via Attack Graphs, Network Flows and Anomaly Detection, Web Application Firewalls, Wireless IDS/IPS, Physical Intrusion Detection for IT, Geospatial Intrusion Detection, Visual Data Communications, Return on Investment: Business Justification, Bro Installation Guide, Index.